Stunting prevention efforts through integrative socialization and counseling programs in Karangwangi Village Cianjur Regency - Shafira Rahmayanti Setiavi; Tania Julyandini (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2024)
In 2016, stunting caused 2.2 million child deaths worldwide. Indonesia ranks 115 out of 151 countries with the highest stunting prevalence globally in 2022. In the West Java region, especially in Cianjur Regency, the stunting rate has decreased from 33.7 percent in 2021 to 13.6 percent in 2022. In Karangwangi Village, Ciranjang District, in 2023, 6 children were found who were indicated to be stunted. Various factors, both direct and indirect factors cause stunting cases. One of the main factors that prevent stunting is the role of a mother. So this service program is realized in the form of stunting socialization which aims to increase awareness of mothers in Karangwangi Village about stunting and clean and healthy living behavior for children as an effort to help realize the creation of individuals with a clean and healthy environment. Both of these programs have been held at Posyandu, PAUD, and also elementary schools located in Karangwangi Village.   Abstrak Pada tahun 2016 kasus stunting menyebabkan 2,2 juta kematian anak diseluruh dunia. Indonesia sendiri menempati peringkat 115 dari 151 negara dengan angka prevalensi stunting tertinggi secara global di tahun 2022. Di wilayah Jawa Barat khususnya di Kabupaten Cianjur, angka stunting mengalami penurunan dari 33,7 persen pada tahun 2021 menjadi 13,6 persen pada tahun 2022. Di Desa Karangwangi, Kecamatan Ciranjang, pada tahun 2023 ditemukan 6 anak yang terindikasi stunting. Kasus stunting disebabkan oleh berbagai faktor, baik faktor langsung maupun faktor tidak langsung. Salah satu faktor utama untuk mencegah terjadinya stunting yakni peran seorang ibu. Maka dari itu, program pengabdian ini diwujudkan dalam bentuk sosilisasi stunting yang bertujuan untuk meningkatkan kesadaran para ibu di Desa Karangwangi mengenai stunting dan perilaku hidup bersih dan sehat bagi anak-anak sebagai upaya membantu mewujudkan terciptanya individu dengan lingkungan yang bersih dan sehat. Kedua program ini telah dilangsungkan di Posyandu, PAUD, dan juga sekolah dasar yang berlokasi di Desa Karangwangi.   Kata Kunci: pola hidup bersih dan sehat, gizi, penyuluhan stunting